Oral health in children with special needs - Mandić, Jelena Čedomir; Jovanović, Svetlana; Mandinić, Zoran; Ivanović, Mirjana; Kosanović, Dušan; Miličić, Biljana; Živojinović Toumba, Vesna (Vojnosanitetski pregled, 2020)
Abstract Background/Aim. Due to their primary medical condition, children with special needs often display lower levels of oral hygiene, larger prevalence of caries and other oral diseases. The aim of this study was to estimate the prevalence of dental caries, oral cleanliness and presence of malocclusion in children with disabilities, as well as to evaluate eruption time of the permanent molars. Methods. Case–control study was carried out on a group of 107 children with disabilities at the Faculty of Dental Medicine, University of Belgrade, Serbia. The control group comprised of 104 healthy school children. Results. Children with disabilities had statistically higher mean [decayed missing and filled teeth – dmft for primary DMF for permanent dentition (dmft DMFT)] values in both dentitions than children from the control group (p < 0.05). Oral cleanliness level was much lower in children with disabilities. A significantly higher percentage of Class II malocclusions and a higher tendency to have a delayed time of eruption of permanent molars were observed in the test group in permanent dentition. Conclusion. Considering poor oral health status and higher tendency for development of malloclusions and delayed eruption, it is necessary to develop preventive dental programmes for children with special needs, as well as improve public awareness about these issues.